Aristotle's lobster: the image in the text - Lieven, Alexander Fürst von; Humar, Marcel; Scholtz, Gerhard (Crustaceana, 2021)
The Anatomai, a lost work written by Aristotle, must have contained a collection of various drawings and figures of species as well as their organs. In his texts (mainly the Historia animalium), Aristotle is often referring to the drawings after the description of species. Our study applies the method of the comparative view (‘Vergleichendes Sehen’) to provide an access to and reconstruction of Aristotle’s lost illustrations based on his textual descriptions. As an example, we chose the treatment of the European lobster (Homarus gammarus L., 1758) in the Aristotelian corpus as a case study. First, we analyse the etymology of the Greek term astakós referring to the lobster and provide an overview on the putative synonyms. Second, we confront the textual basis of the description with several questions concerning the degree of abstraction, the relation between text and image, and the spatial orientation of the image. Finally, we present a step-by-step reconstruction of Aristotle’s illustrations of the lobster based on the various passages dealing with its anatomy in the text of the Historia animalium. The problems which arise by a confrontation of the textual basis with hypothetical images are discussed at a more general level. We conclude that this kind of a text-based image reconstruction is only possible if the object described by Aristotle is unambiguously identifiable and still visually accessible.